Analisis Sistem Rujukan Jaminan Kesehatan Nasional RSUD. Dr. Adjidarmo Kabupaten Lebak - Primasari, Karleanne Lony (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2015)
National Health Insurance (NHI) is the implementation of the Law. 40 year 2004 on National Social Security System in the field of healthcare with the concept of Universal Health Coverage (UHC) that forced participants to follow a tiered referral system to get comprehensive health care, cheap, affordable but good quality. The ineffectiveness of the referral system in Indonesia gives impact on the accumulation of patients in healthcare facilities resulting in the utilization of advanced skilled providers and advanced equipments are inappropriate and the declining quality of health care. This study used a qualitative approach, the analytical methods used of content analysis are based on method triangulation , source triangulation and data triangulation. The results of the study were divided into two components, namely the medical referral system characteristics and tiered referral system. In medical referral system characteristics, NHI led to improvements in the implementation of a referral system in Dr. Adjidarmo Hospital although it is not too significant. While in the and tiered referral system components, improvements existed in the aspect of policy and procedures, so that a strong effort is still needed to improve other aspects of creating a better referral system. It is expected that the results of this study may be one of the input for the hospital management and related institutions in improving various aspects related to the successful implementation of a tiered referral system in Lebak District in order to achieve Universal Health Coverage (UHC) in Indonesia.